AVALIAÇÃO DO ÓLEO DE PEIXE RICO EM OMEGA-3 EM INFECÇÕES CAUSADAS POR Escherichia coli ENTEROAGREGATIVA 042. - CÂMARA, Thalita de Albuquerque Véras (2022)
The intestinal microbiota is defined as a microorganism population that inhabit the gastrointestinal tract. This population is involved in essential functions for host homeostasis, such as digestion and nutrients synthesis, cell integrity, development of immune system, barrier against pathogens. Escherichia coli is a commensal microorganism present in the intestine, however, in the presence of a bacteria population imbalance it can be responsible for causing several pathologies and disorders. The aim of this study was to evaluate the activity of fish oil rich in omega-3 against Escherichia coli infections. Initially, in vitro tests were performed to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) using a microplate dilution technique. The cell cytotoxicity assay was performed to evaluate a possible effect of fish oil on HT-29 intestinal cells. For in vivo tests, Tenebrio molitor larvae were used to assess toxicity, as well as Swiss mice to evaluate the oil effect on pathogenic E. coli intestinal colonization. In order to evaluate the oil effect on colonization, animals were infected with E. coli and treated with fish oil throughout the experiment. Colony-forming units (CFU/g) obtained from fresh feces were counted for 15 days after animal infection. In addition, a histological analysis of the liver, kidney and gut (colon) was performed to assess possible morphological changes, such as: congestion, inflammatory infiltrate and necrosis. The results showed a MIC of 25.0 mg/mL and MBC of 100 mg/mL. In the cell cytotoxicity assay, fish oil was toxic only at a concentration of 100 mg/mL. In the in vivo test using T. molitor larvae, it was possible to observe an improvement in the survival of the group treated with fish oil. The colonization assay showed lower values of UFC / g for several days of the experiment in the group treated with the oil against the infected and untreated group, with a statistical difference starting on the 7th day. The histological analysis revealed that in the infected animals the predominant degree of the inflammatory infiltrate was moderate in the intestine and only in this group the same process was observed in the liver. There was no progress in hepatic hydropic degeneration in the animals of treatment group and the profile of the inflammatory infiltrate was mild. It was found that fish oil was effective in terms of its bacteriostatic effect, since it controlled E. coli colonization and additionally, according to the histology results, it improved the intestinal cells cellular integrity.